An Update on the New Approaches in Healthcare Marketing - Alkhatib, Ahed J; Al-Balas, Samir (International Journal of Molecular Microbiology, 2021)
There has been a shift in marketing thinking in the health sector as a result of shifts in consumer and societal conduct. The concept of health as a good rather than a service has been recently promoted. The main objective of this study was to review the updated literature about the new approaches in healthcare marketing. The study's key findings revolve around the economic axis that shifts services into products. Health care has become a commodity and a need in this sense, and the patient, as a client, should define his needs and demands. Taken together, Health marketing has elevated the status of healthcare by transforming the idea of a healthy environment serving patients into a health agency with a financial effect.